Studi Deskriptif: Sikap, Pengawasan Keluarga, Tingkat Pengetahuan dan Upaya Pengendalian Hipertensi Pada Lansia - Novita Nirmalasari; Yessi Angga Novitasari (Poltekkes Kemenkes Surakarta, 2020)
Background: Elderly is a decrease in cardiovascular function. Sstructural and functional changes occur in the peripheral vascular system responsible for variations in blood pressure. The study aims at finding out attitude, family supervision, level of knowledge, and efforts to control hypertension in working area Puskesmas Saptosari Gunungkidul. Method: The study was descriptive research with cross-sectional. Samples were selected using a purposive sampling. The number of the sample 38 repondent. The research instrument used a questionnaire. The data analysis used was univariate. Result: The majority of women (94.7%), aged 60-70 years (84.2%), and hypertension stage I (68.4%). Most of the attitudes have the right attitude (94,7%), family supervision (89,5%), and inadequate level of knowledge (76,3%). In controlling efforts, most were in a good category (94,7%). Conclusion: Almost all respondents have the right attitude and supervision from the family. Even though they have an inadequate level of knowledge, control efforts are mostly reasonable.